Mark Fitzgerald and John O’Flynn (eds), Music and Identity in Ireland and Beyond (2014) - Slominski, Tes (Journal of the Society for Musicology in Ireland, 2017)
A review of Mark Fitzgerald and John O’Flynn (eds), Music and Identity in Ireland and Beyond (Farnham: Ashgate, 2014). ISBN 978-1-4724-0966-9.